2002
DOI: 10.1111/j.1547-5069.2002.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Breast Cancer in Jordanian Women

Abstract: Significant differences in correlates of breast cancer were found between the cases and the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The pooled RR for exclusive use of permanent dye was 1.00 (95% CI, 0.94-1.05) and was 0.99 (95% CI, 0.89 to 1.11) for intensive exposure (TABLE 2). There was no substantial difference in pooled RRs This was explained mainly by the result of 1 population-based casecontrol study 32 with an RR of 8.62 and a wide 95% CI, which might be considered as an influential point. Exclud- …”
Section: Breast Cancermentioning
confidence: 76%
“…The pooled RR for exclusive use of permanent dye was 1.00 (95% CI, 0.94-1.05) and was 0.99 (95% CI, 0.89 to 1.11) for intensive exposure (TABLE 2). There was no substantial difference in pooled RRs This was explained mainly by the result of 1 population-based casecontrol study 32 with an RR of 8.62 and a wide 95% CI, which might be considered as an influential point. Exclud- …”
Section: Breast Cancermentioning
confidence: 76%
“…Six studies [5,8,[11][12][13]20] reported oral contraceptive use as a risk factor for breast cancer in our study. The result is consistent with other early meta-analysis.…”
Section: Oral Contraceptive Usementioning
confidence: 91%
“…Thus, there were a total of 15 potential independent studies for analysis, which are listed in Table 1. Fifteen studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] were included in the meta-analysis on the association between reproductive factor, oral contraceptive use, breast-feeding and breast cancer risk. According to the summary OR based on two identified reproductive factors, including number of full-term pregnancy≥1 and menopausal age > 50 yr, oral contraceptive use was associated with the increase in breast cancer risk; however, the summary OR based on breastfeeding indicated no association with breast cancer risk ( Table 2, Fig.…”
Section: Source Of Referencesmentioning
confidence: 99%
“…A total of 11 case-control studies (7, 2434) and four cohort studies (16, 1820, 35) have investigated the relationship between personal hair dye use and risk of breast cancer (Table 2). Nearly all of the studies have yet to suggest a conclusive no association between breast cancer risk and exposure to hair dyes with the exception of one case-control study (34).…”
Section: Breast Cancermentioning
confidence: 99%
“…Nearly all of the studies have yet to suggest a conclusive no association between breast cancer risk and exposure to hair dyes with the exception of one case-control study (34). …”
Section: Breast Cancermentioning
confidence: 99%